A new species of Aboilus (Insecta, Orthoptera, Prophalangopsidae) from the Middle Jurassic of Daohugou, Inner Mongolia, China - Fang, Yan; Zhang, Haichun; Wang, Bo (Zootaxa, 2009)
A new species, Aboilus chinensis sp. nov., is described and attributed to Aboilus (Insecta, Orthoptera, Prophalangopsidae, Aboilinae), from the Middle Jurassic of Daohugou in Inner Mongolia, China. The tegminal diagnostic characters for Aboilus Martynov, 1925 are revised. The fossil record of Aboilus from China is reviewed.